Excesiva onerosidad, hardship y cláusula hardship - García Long, Sergio (Pontificia Universidad Católica del Perú, 2024)
From a comparative and transnational perspective, this work focus on the phenomenon of unexpected circumstances in contracts, and specifically, on hardship and the various models of hardship proposed by (i) civil codifications, (ii) international uniform law instruments, and (iii) international contractual practice. The pandemic made hardship fashionable, but with that was revealed that hardship was not really understood. To fix that, it is needed a study which includes the three levels of analysis aforementioned and to distinguish between excessive onerosity, hardship and hardship clause. Only this will allow to understand the real extension of hardship in contracts and the interaction of its models between Civil Law and Common Law.

Desde una perspectiva comparada y transnacional, este trabajo se enfoca en el fenómeno de las circunstancias inesperadas en el derecho de contratos, y en específico, sobre la hardship y los diversos modelos de hardship propuestos por (i) las codificaciones civiles, (ii) los instrumentos internacionales de derecho uniforme, y (iii) la práctica contractual internacional. La pandemia hizo que la hardship se ponga de moda, pero con ocasión de ello se observó que la hardship no era realmente comprendida. Para corregir lo anterior es necesario un estudio que tenga en cuenta los tres niveles de análisis mencionados y que permita distinguir entre excesiva onerosidad, hardship y cláusula hardship. Solo así se entenderá la verdadera extensión de la hardship en los contratos y la interacción de sus modelos entre el Civil Law y Common Law.
Excessive onerosity, hardship and hardship clause
Keywords: Contracts; Unexpected circumstances; Excessive onerosity; Hardship; Hardship clause; Contratos; Circunstancias inesperadas; Excesiva onerosidad; Hardship; Cláusula hardship; https://purl.org/pe-repo/ocde/ford#5.05.00